FACTORS THAT INFLUENCE TOEFL GRADUATION LEVEL IN INTENSIVE TOEFL TRAINING PROGRAM FOR ENGLISH STUDY PROGRAM STUDENTS AT STAIN BENGKALIS - Salwa binti Ayub; Rini Fitria Satria (Elite : English and Literature Journal, 2018)
This study provides an overview of the factors that influence the level of TOEFL graduation of English Study Program students in the Intensive TOEFL Training Program.  The purpose of this study is to conduct an empirical investigation whether the factors variable affect the variable of TOEFL graduation level. The total populations in this study were 113 respondents. The data were collected through questionnaires. Data analysis was done by multiple regressions using SPSS version 22. The result showed that the factors simultaneously affect the level of TOEFL graduation.